Phonological Processing in Human Auditory Cortical Fields - Woods, David L.; Herron, Timothy; Kang, Xiaojian; Cate, Anthony D.; Yund, E. William (Frontiers in Human Neuroscience, 2011)
We used population-based cortical-surface analysis of functional magnetic imaging (fMRI) data to characterize the processing of consonant-vowel-consonant syllables (CVCs) and spectrally-matched amplitude-modulated noise bursts (AMNBs) in human auditory cortex as subjects attended to auditory or visual stimuli in an intermodal selective attention paradigm. Average auditory cortical field (ACF) locations were defined using tonotopic mapping in a previous study. Activations in auditory cortex were defined by two stimulus-preference gradients: (1) Medial belt ACFs preferred AMNBs and lateral belt and parabelt fields preferred CVCs. This preference extended into core ACFs with medial regions of primary auditory cortex (A1) and rostral field (R) preferring AMNBs and lateral regions preferring CVCs. (2) Anterior ACFs showed smaller activations but more clearly defined stimulus preferences than did posterior ACFs. Stimulus preference gradients were unaffected by auditory attention suggesting that different ACFs are specialized for the automatic processing of different spectrotemporal sound features.